Humanity, Nature, and the Supernatural in Washington Irving’s “The Legend of Sleepy Hollow” - Sabri Mnassar (European Journal of American Studies)
This paper examines the ways through which Washington Irving’s “The Legend of Sleepy Hollow” might be considered as an example of environmental literature which focuses extensively on nature and the human relationship to it. It argues that Irving promotes an ecocentric worldview which treats human beings as members rather than masters of the natural environment. It suggests that this worldview is articulated in various ways in the tale such as the emphasis on the intrinsic value of nature, the celebration of biodiversity, and the condemnation of the anthropocentric outlook on the natural world. In its study of Irving’s representation of the natural environment, the essay claims that nature is portrayed as a character that is not only omnipresent but also more powerful than human beings and their attempts to dominate and subdue it. It asserts that the supernatural in the tale is only nature’s reaction to human greed and egotism. Due to the presence of many important environmental values and ethics, the paper argues that the story reflects Irving’s ecological awareness and underlines his significant contribution to the development of environmental literature.